Substantial and Disseminated Matoš - Medve, Zoltán A. (Poznańskie Studia Slawistyczne, 2014)
This paper deals with the literary works of A.G. Matoš. It attempts to demonstrate that in his works a whole period of the Croatian literature modernism is concentrated. It also explores a question: Why cannot the opus of this Croatian author be absorbed into the Hungarian literature? In the Hungarian literature of modernism Matoš would be disseminated first of all because of his strong literary authority and his very special language use. Despite difficulties, the author of this paper finds some parallels between Matoš and the Hungarian authors of modernism. As a coherent and strong author of extraordinary fantasy, languge usage and style, Matoš can be only partly assimilated into the Hungarian literature.